Influence of Tertiary Institution Attended and Academic Factors on Graduate Employability in Ogun State Civil Service, Nigeria - OLANIYI, Olusegun Samuel; SALOMI, Modupe Olufemi; JESUBUNMI, Ifeoluwa Phebe (Ilorin Journal of Education, 2025)
The widening disparity between the type of tertiary institution attended, academic-related factors, and graduate employability has raised concerns about the equal valuation and preparedness of graduates from universities, polytechnics, monotechnics, and colleges of education for civil service roles. This study investigated the influence of tertiary institution attended and academic factors on graduate employability within the Ogun State Civil Service. A descriptive research design of the survey type was adopted. The population comprised 424 directors across 86 Ministries, Departments, and Agencies (MDAs), from which a sample of 86 directors was purposively selected. Data were collected using three validated instruments tagged: Tertiary Institution Attended Questionnaire (TIAQ), Academic Factors Questionnaire (AFQ) and Graduate Employability Scale (GES) with reliability coefficients of .80, .77, and .84, respectively. Results indicated university graduates were predominantly employed (X̅ = 3.14, SD = .877), all graduate categories were in high demand (X̅ = 2.56–3.65; SD = .426–.837), class of degree influenced employability (X̅ = 2.73, SD = .979), but only academic discipline had significant relative influence (β = .361, t = 3.475, p < .05). A joint significant effect was found (F (3, 77) = 6.655; p < .05). The study concluded that enhancing curriculum relevance, fostering industry collaborations, and promoting equitable access to quality education are critical for improving graduate employability and it was recommended among others that curricular reforms and integration of professional certifications should be incorporated to enhance graduate readiness.